2011
DOI: 10.1093/ecam/nep035
|View full text |Cite
|
Sign up to set email alerts
|

Cupping for Treating Pain: A Systematic Review

Abstract: The objective of this study was to assess the evidence for or against the effectiveness of cupping as a treatment option for pain. Fourteen databases were searched. Randomized clinical trials (RCTs) testing cupping in patients with pain of any origin were considered. Trials using cupping with or without drawing blood were included, while trials comparing cupping with other treatments of unproven efficacy were excluded. Trials with cupping as concomitant treatment together with other treatments of unproven effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
109
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(116 citation statements)
references
References 15 publications
0
109
0
7
Order By: Relevance
“…In the present study, the mean reduction of bleeding in the cupping group during 2 months was estimated approximately as 357 units, which represents a considerable effect of this intervention. Although the effect of cupping on menstrual bleeding was examined only in the mentioned study and the present research, the impact of this intervention on a variety of outcomes (such as pain, hypertension, and rehabilitation of limbs) has been evaluated in several studies, of which the majority have confirmed the effectiveness of cupping (7,8,23). In gynecological studies, the effect of cupping on pain following delivery and dysmenorrhea has been approved (11).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the present study, the mean reduction of bleeding in the cupping group during 2 months was estimated approximately as 357 units, which represents a considerable effect of this intervention. Although the effect of cupping on menstrual bleeding was examined only in the mentioned study and the present research, the impact of this intervention on a variety of outcomes (such as pain, hypertension, and rehabilitation of limbs) has been evaluated in several studies, of which the majority have confirmed the effectiveness of cupping (7,8,23). In gynecological studies, the effect of cupping on pain following delivery and dysmenorrhea has been approved (11).…”
Section: Discussionmentioning
confidence: 92%
“…The vacuum can be done in different ways (24). Several systematic reviews have been conducted to evaluate the effect of cupping on pain treatment (23,25). The effectiveness of the mechanism of cupping is done through the manipulation of small myelinated peripheral nerve fibers in the muscle along with suction.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent clinical studies have reported positive results of cupping in patients with musculoskeletal diseases e.g. lower back pain [6], carpal tunnel syndrome [7], brachialgia paresthetica nocturna [8], cancer pain [9] and chronic neck pain [10-12]. In China Cupping is widely used and two systematic reviews were recently published about the results [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The latter was measured using several techniques such as a visual analogue scale. In all previous trials, the response rates were higher and pain measurements were lower in cupping groups than in control groups (Kim et al, 2011). All these trials suggested that cupping is a successful pain therapy with promising effects on other illnesses (Shaban, 2011).…”
Section: Physicalmentioning
confidence: 94%